SR AND ND ISOTOPE SYSTEMATICS OF FRANCISTOWN PLUTONIC ROCKS, BOTSWANA: IMPLICATIONS FOR NEOARCHAEAN CRUSTAL EVOLUTION OF THE ZIMBABWE CRATON - Zhai M.; Kampunzu A.B.; Modisi M.P.; Bagai Z. (My University, 2006)
The Francistown plutonic rocks at the south-western margin of the Zimbabwe craton consist of three igneous suites: Sanukitoid, Tonalite–Trondhjemite–Granite (TTG) suites and High-K granites. The TTG suite is subdivided into High Aluminum-TTG (HA-TTG) and Low Aluminum-TTG (LA-TTG) sub-suites. Their Rb–Sr isotope systems were partially homogenized by post-crystallization thermo–tectonic events, in which hydrothermal solutions and migmatization played an important role. Therefore, the Rb–Sr isochron age of 2427±54 Ma can only be regarded as a lower limit to the Francistown plutonic rock age. The large errors in the Sm–Nd isochron dates of Francistown granitoids indicate that these dates are not really constrained. In this study we compared the rock types of Francistown and adjacent areas, adopting the precise U, Th–Pb single zircon SHRIMP ages from the Vumba area as references. For TTG and Sanukitoid suites, the age we adopted is ca. 2.7 Ga, which is close to their depleted-mantle Sm–Nd model ages (T DM). For High-K granites, the age adopted is ca. 2.65 Ga, which is also close to their Sm–Nd isochron age. The highest ε Nd values of Sanukitoids and TTG are +2.1 and +2.3, respectively. The positive ε Nd values and trace element geochemistry support partial melting of a depleted mantle and young oceanic crust for the genesis of Sanukitoid and the TTG suites respectively. The lowest ε Nd values of Sanukitoids and TTGs are −1.0 and −1.1, respectively, indicating contamination by continental crust, up to 10 and 14%, respectively. The ε Nd values of TTG decrease with decreasing Al2O3 and Sr contents and increasing Eu negative anomalies (Eu*–Eu), suggesting that the TTG magmas underwent a coupled fractionation crystallization and crustal contamination, and that the LA-TTG was the product of the fractionation and contamination of the HA-TTG sub-suite. In contrast, negative ε Nd values for the High-K granites (from −0.4 to −3.5) indicate the involvement of LA-TTG and some materials from an old continental crust in their genesis. The products of partial melting of both oceanic and continental crusts at the south-western margin of the Zimbabwe craton occurred within a short time interval (from 2.7 to 2.65 Ga ago) suggesting that the Francistown plutonic rocks were formed in a active continental margin environment, where a young ocean plate (Limpopo oceanic plate) subducted underneath an old continental plate (Zimbabwe craton).
Keywords: RB-SR ISOTOPES; SM-ND ISOTOPES; PETROGENESIS; TECTONIC EVOLUTION; ARCHAEAN TTG-SANUKITOID-HIGH-K GRANITES; FRANCISTOWN; BOTSWANA; Precambrian::Archean::Neoarchean; Докембрий::Архей::Неоархейская